Transformasi Sektor Ekonomi DKI Jakarta: Analisis LQ, Tipologi Klassen dan Shift Share - Dafis Israndi Nasution; Benardin (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study identifies economic sectors with comparative advantages and that contribute significantly to regional economic growth. Secondary data used in this study are the GDP value of DKI Jakarta Province and Indonesia's GDP at constant prices from 2017 to 2023. The research methodology used is LQ Analysis, Klassen Typology and Shift Share Analysis. Based on the results of the study, in 2017 there were four sectors that supported the economic activities of DKI Jakarta Province, while in 2023 there were three main sectors. In addition to providing in-depth information on the potential areas for regional economic development plans, this study also provides useful guidance for policy makers and other relevant stakeholders to create inclusive and sustainable economic development plans.